THE INFLUENCE OF NOISE ON COGNITIVE PERFORMANCE - Chandra, Huki; Wahyuni, Ayu Endah (Journal of Industrial Engineering Management, 2024)
Human performance is affected by several factors related to work and workplace conditions, including occupational noise.  Noise can affect work and mental performance parameters such as memory, attention, concentration, and reaction time. Reaction time in response to a situation can significantly impact our lives because of its practical implications. Environmental noise invades the learning space and has a negative effect on students' cognitive performance. This study considers the presence of noise factors on students' cognitive performance. High cognitive performance is needed by students, especially in lecture material that requires high memory. Aspects of cognitive ergonomics are included in this study because it examines how people interact with noisy environments. In this study, measuring cognitive performance was carried out by measuring reaction time, number memory performance, and sequence memory performance. Based on the statistical tests in this study, it can be concluded that there is no significant effect of gender on reaction time, number memory, and sequence memory in conditions with noise and without noise. The presence of noise can significantly reduce the performance of sequence memory. Number memory performance decreases in the presence of noise, but not significantly. The reaction time required to respond to the stimulus is longer in the presence of noise, but not significant.